ANALISIS PERLINDUNGAN HUKUM TERHADAP BEKAS ISTERI PADA PUTUSAN HAKIM WILAYAH PENGADILAN AGAMA KOTA PADANG - Yusdian, Desi; Al Ikhlas, Al Ikhlas; Firdaus, Firdaus (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2024)
Researchers are interested in examining decisions as a comparison from year to year starting from 2020-2022 regarding the decisions of Religious Court judges which contain legal protection for wives and analyzing the role of judges in Religious Courts in protecting and determining husbands' responsibilities towards ex-wives after divorce. The aim achieved in this research is to analyze legal protection for ex-wives after divorce in the Padang City Religious Court area. This form of research is mixed method research. Meanwhile, the type of research is library research (library review). This research approach is normative juridical in nature. This research was conducted at the Padang Religious Court in the period 2020-2022. In analyzing the data that has been collected, the model used is an interactive model. The interactive model in question consists of data reduction, data presentation and drawing conclusions or verification. The findings of this research are that legal protection for ex-wives in the Padang City Religious Court area is still low. This is proven by the lack of decisions containing the rights of ex-wives after divorce, namely at 5.7%, 6.5% and 7.5%, which is below 10% of the total number of divorce decisions for talak and contested divorce in time span 2020-2022. The reason why there are so few decisions containing the rights of ex-wives after divorce is due to the existence of legal regulations which state that judges are not permitted to make dictums in rulings that exceed the demands (ultra petita) and the wife's lack of knowledge about the procedures for fulfilling her rights in the judicial process